Biomechanical Evaluation of the Femoral Neck System in Unstable Pauwels III Femoral Neck Fractures: A Comparison with the Dynamic Hip Screw and Cannulated Screws. Issue 3 (March 2017) - Stoffel, Karl; Zderic, Ivan; Gras, Florian; Sommer, Christoph; Eberli, Ursula; Mueller, David; Oswald, Martin; Gueorguiev, Boyko
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To evaluate the biomechanical performance of femoral neck system (FNS) in comparison with established methods for fixation of femoral neck fractures in a cadaveric model. Methods: Twenty pairs of fresh-frozen human cadaveric femora were instrumented either with dynamic hip screw and antirotation screw (DHS-screw), DHS-blade, 3 cannulated screws (3CS) or with FNS in a partially paired design. The specimens were randomized to 2 paired treatment groups based on the bone mineral density (BMD), namely DHS-screw/DHS-blade and FNS/3CS. A reduced unstable femoral neck fracture with postero-caudal comminution, OTA/AO 31–B2.3, 70 degrees Pauwels III, was simulated by cutting 30 degrees distal and 15 degrees posterior wedges. Cyclic axial loading was applied in 16 degrees adduction, starting at 500 N and with progressive peak force increase of 0.1 N/cycle until construct failure. Axial stiffness was measured in the third loading cycle. Femoral neck and leg shortening, and varus tilting and implant migration were calculated by means of optical motion tracking. Results: Mean axial stiffness was 688.8 ± 132.6 N/mm for DHS-screw, 629.1 ± 94.1 N/mm for DHS-blade, 748.9 ± 211.4 N/mm for FNS, and 584.1 ± 156.6 N/mm for 3CS, with no statistical significances. Cycles until 15-mm leg shortening were comparable for DHS-Screw (20, 542 ± 7465), DHS-blade (19, 161 ± 3793) and FNS (17, 372 ± 2996), however significantly higher than for 3CS (7293 ± 2819), P < 0.001. Similarly, cycles until 15 mm femoral neck shortening were comparable between DHS-screw (20, 846 ± 7339), DHS-blade (18, 974 ± 4032) and FNS (18, 171 ± 2585), and significantly higher than 3CS (8039 ± 2778), P < 0.001. Conclusions: From a biomechanical point of view, the femoral neck system is a valid alternative to treat unstable femoral neck fractures, representing the advantages of a minimally invasive implant with comparable stability to the 2 DHS systems and superior to cannulated screws.